Effects of aeration rate on maturity and gaseous emissions during sewage sludge composting. (October 2016) - Yuan, Jing; Chadwick, David; Zhang, Difang; Li, Guoxue; Chen, Shili; Luo, Wenhai; Du, Longlong; He, Shengzhou; Peng, Shengping
Highlights: The low and moderate aeration rates (AR) had high maturity and humification. The high AR did not form mature compost during sewage sludge composting. The moderate AR had the highest NH3 emissions. The low AR had the highest CH4 and N2 O emissions. The recommended AR for sludge composting is 0.2 L·kg −1 DM·min −1 . Abstract: This study investigated effects of aeration rate (AR) on maturity and gaseous emissions during sewage sludge composting, sewage sludge and corn stalks as the bulking agent were co-composted at different ARs (0.1, 0.2, 0.3 L·kg −1 dry matter (DM)·min −1 ). The thermophilic phase for the low and moderate AR treatments was able meet sanitation requirements, but too short to meet sanitation requirements in the high AR treatment. The high AR treatment was significantly different from the other treatments, and had the lowest electrical conductivity and highest E4 /E6 (absorbance ratio of wavelength 465 and 665 nm). The AR influences the nitrogen variations; high AR compost had the highest NH4 + -N content and lowest NOx − -N content. The AR was the main factor influencing compost stability, but the AR had little impact on pH and the germination index. The moderate AR treatment had the highest NH3 emissions during composting, while the low AR treatment had the highest CH4 and N2 O emissions. Based on our comprehensive investigation, the recommended AR for sludge composting is 0.2 L·kg −1 DM·min −1 .